Pengaruh Kesadaran Lingkungan Terhadap Subjective Well Being Dalam Pengelolaan Sampah Di Dalam Kelas Pada Siswa Sekolah Menengah - Ramadhayanti, Novializa; Pramesti, Regita Khairani; Oktavira, Adelia Chika; Saputra, Ardian Firdaus; Prastiwi, Difani Cahya; Alifianto, Muhammad Farid; Arrazi, Rahma Meilina; Abdillah, Rijal (Innovative: Journal Of Social Science Research, 2024)
To preserve the environment, action must be taken by all members of society. Awareness of the importance of a healthy, clean environment, and is known as environmental awareness. Environmental awareness is a psychological state where a person is aware of problems that must be overcome in interacting with the environment. Be useful in environmental conservation. Individual involvement in creating a sustainable environment through environmental awareness can provide benefits to individual subjective well-being. This research method uses a quantitative approach, using the SPSS data analysis program and a Likert scale as criteria for subjective well-being and environmental awareness among students. The goal is to understand how to manage waste, and each statement on this site has its own challenges. And stated. This is in accordance with the research objective to understand the impact of environmental factors on subjective well-being in student assessments. Validity tests are carried out to ensure that the tools used meet the standards required to obtain accurate data. Data was obtained from a questionnaire with 113 respondents. The results of this research are that environment-based variables have no effect on waste management maintenance variables, but variables based on subjective experience have a significant effect on waste management maintenance variables.